Análisis de las normativas para el diseño y construcción de redes eléctricas de media y baja tensión de las empresas distribuidoras del Ecuador - Remache Campoverde, Alexis Daniel (2023)
Electricity service is supplied in the Ecuadorian territory through ten electrical companies, which have established various parameters for the design, presentation, and approval of electrical projects; these are adapted and approved to the requirements and conditions of each sector. Therefore, the present research work called "Analysis of the regulations for the design and construction of medium and low voltage electrical networks of the distribution companies of Ecuador" has as its main objective to analyze the methodologies for the design and construction of medium and low voltage electrical networks, in force in Ecuador. This study is a bibliographic type and qualitative nature, for which the bibliographic compilation of all the regulations in force in Ecuador and of two international companies such as Colombia and the Dominican Republic was carried out; for the comparative process, the graphic scales method was used, assigning ratings between each design parameter. It is identified that the rules for distribution systems (Part A) of the Electric Company of Quito present a higher qualification with respect to the others, in the same way, the technical standards for electrical installations of the energy company of Pereira-Colombia, is the one whith the least international qualification. Keywords: design regulations, medium and low voltage, electrical networks,